Haley Ruybal: capstone - Ruybal, Haley, artist (Colorado State University. Libraries, 2013)
The artist's statement: Throughout my life I have made it my goal to make beautiful things for people to enjoy, but I have come to realize that beauty alone does not get anyone very far. Along with my passion for the arts, I am very aware of the privileges and disadvantages that I have both as a woman, and more specifically as an indigenous woman. I am intrigued by the ways that my two passions collide and have a much farther reach than simply focusing on just one or the other. By bringing my desire for social justice and my skills as an artist together, I hope to bring greater awareness to the issues facing both Indigenous peoples and communities that are not generally talked about or taught. My sincere hope is to be able to start a conversation about tribal sovereignty, race and commonly held misconceptions that permeate American society. In my most recent series Colonization, I discuss the ways in which individual objects can be used to describe specific spaces in time in relation to the colonization of Indigenous populations in America. This three-piece series highlights pre-, post- and de-colonial ideas and ways of thinking to shed light on the issues of historical trauma and invisibility of Indigenous issues and people in the larger American society. These works are a tactile representation of the effects of colonization on individuals as well as on broader, societal ideology.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.